2005
DOI: 10.1161/01.str.0000189998.74892.24
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Blood Pressure Profiles as Predictors of Long-Term Outcome After Acute Ischemic Stroke

Abstract: Background and Purpose-Most patients have elevated blood pressure (BP) in the early phase after an acute ischemic stroke. Mechanism and effects of this BP elevation are not well understood. The benefits of intervention by lowering the initial BP or waiting for spontaneous return to normal values remain debated. We studied the hypothesis that increased BP level and profile variability will adversely affect long-term outcome after stroke with and without thrombolytic treatment. Methods-We studied the 615 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
90
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 32 publications
4
90
4
Order By: Relevance
“…34,37,41 We did not find an association between BP variability during the first 24 hours and short-and long-term outcome. In patients with acute stroke treated with intravenous thrombolysis, high BP variability led to a poor outcome.…”
Section: -31contrasting
confidence: 68%
See 3 more Smart Citations
“…34,37,41 We did not find an association between BP variability during the first 24 hours and short-and long-term outcome. In patients with acute stroke treated with intravenous thrombolysis, high BP variability led to a poor outcome.…”
Section: -31contrasting
confidence: 68%
“…The rate of elevated BP during acute stroke in our study was lower than the rate described by others. 23,36,37 The low rate of elevated BP during acute stroke may be because of the older age of our patients, and the fact that we used 24H BPM. 38 It is possible that very old subjects exhibit a smaller protective increase in BP during acute stroke.…”
Section: -31mentioning
confidence: 99%
See 2 more Smart Citations
“…Yong et al reported the effect of blood pressure before and after t-PA injection on cerebral hemorrhage and patient prognosis, using the patient cohort in the ECASS study. The results obtained with the cohort from the first ECASS study indicated that Higher systolic BP or diastolic BP at baseline were associated with favorable outcome assessed on modified mRS at 90 days, lower within-patient 0-to 72-hour average SBP or DBP implied favorable outcome, and reduced variability of 0-to 72-hour DBP profile was an independent predictor of favorable outcome 5 . The results obtained with the cohort from the second ECASS study showed that higher systolic pressure before t-PA injection, higher maximum/average systolic pressure for 24 hours post-injection, and larger changes in systolic pressure were associated with higher frequency of cerebral hemorrhage and worsening of neurological symptoms by day 7 from the initial attack 6 .…”
Section: Introductionmentioning
confidence: 96%